2021
DOI: 10.3390/ma14164375
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Related Temperature Thresholds in FSSW of Aluminium Alloys

Abstract: Friction Stir Spot Welding (FSSW) is assumed as an environment-friendly technique, suitable for the spot welding of several materials. Nevertheless, it is consensual that the temperature control during the process is not feasible, since the exact heat generation mechanisms are still unknown. In current work, the heat generation in FSSW of aluminium alloys, was assessed by producing bead-on-plate spot welds using pinless tools. Coated and uncoated tools, with varied diameters and rotational speeds, were tested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In this way, they concluded that the AZ31-fly ash composite possesses higher wear resistance as compared to AZ31 alloy [150]. It is evident that FSW and FSP techniques could have beneficial impacts on the mechanical behavior of Mg and other metallic alloys [133,[151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]. Hence, the mechanical properties of some types of magnesium-based alloys before and after FSP are listed in Table 7.…”
Section: Mechanical Performancementioning
confidence: 99%
“…In this way, they concluded that the AZ31-fly ash composite possesses higher wear resistance as compared to AZ31 alloy [150]. It is evident that FSW and FSP techniques could have beneficial impacts on the mechanical behavior of Mg and other metallic alloys [133,[151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]. Hence, the mechanical properties of some types of magnesium-based alloys before and after FSP are listed in Table 7.…”
Section: Mechanical Performancementioning
confidence: 99%
“…A study was conducted by Andrade et al on shoulder-related temperature thresholds in FSSW of aluminum alloys. The research results indicate that the temperature in FSSW can be regulated by using an appropriate combination of rotation speed and tool dimensions for aluminum alloys (Andrade et al, 2021). The heat generation in aluminum alloy FSSW was assessed by producing bead-on-plate spot welds with a pinless tool.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding (FSW) does not exhibit the melting and solidification phase of joining the materials and so the problems encountered during the fusion welding process will be overcome [9][10][11]. Demonstrations of the joining of dissimilar combinations like Al-Fe [12], Al-Cu [13], Al-Brass [14], and dissimilar Al-Al [15] joints were attempted by various researchers.…”
Section: Introductionmentioning
confidence: 99%